Yield and flow properties of ultra-fine, fine, and coarse grain microstructures of FeCoNi equiatomic alloy at ambient and cryogenic temperatures. (June 2023) - Lavakumar, Avala; Yoshida, Shuhei; Punyafu, Jesada; Ihara, Shiro; Chong, Yan; Saito, Hikaru; Tsuji, Nobuhiro; Murayama, Mitsuhiro
Abstract: The current study reveals the Hall-Petch relationship, or mean grain size control, and flow properties of equiatomic FeCoNi alloy having different grain sizes at room temperature (298 K) and cryogenic temperature (77 K). For the first time, various mean grain sizes ranging from the ultra-fine regime (0.7 μm) to the coarse grain regime (145.3 μm) were achieved in a FeCoNi alloy by high-pressure torsion and subsequent annealing. The tensile yield strength depends strongly on temperature and grain size. Hall-Petch plots demonstrate that the grain boundary strength coefficient is insensitive to the temperature, whereas friction stress increases as the temperature decreases. For all the grain sizes both strength and ductility were increased with decreasing the temperature down to 77 K. Dislocation slip is responsible for the room temperature mechanical properties. At cryogenic temperature, on the other hand, nano twinning appears as an additional deformation mechanism in addition to the dislocation slip. Graphical abstract: Image, graphical abstract